Impact of long-term use of oral nutritional supplement on nutritional adequacy, dietary diversity, food intake and growth of Filipino preschool children - Dieu T. T. Huynh; Elvira Estorninos; Maria Rosario Capeding; Jeffery S. Oliver; Yen Ling Low; Francisco J. Rosales (Journal of Nutritional Science, 2016)
Nutrient deficiencies during childhood have adverse effects on child growth and health. In a single-arm 48-week long-term intervention, we previously reported the efficacy of oral nutritional supplementation (ONS) and dietary counselling on catch-up growth and growth maintenance in nutritionally at-risk Filipino children. The present analysis was done to assess the contributing effects of ONS to nutritional adequacy, dietary diversity, food intake and longitudinal growth. ONS (450 ml) was consumed daily providing 450 kcal (1880 kJ) and at least 50 % of micronutrient requirements among 200 children aged 3–4 years with weight-for-height percentiles between 5th and 25th (WHO Growth Standards). Weight, height and dietary intakes using 24-h food recalls were measured at baseline, and at weeks 4, 8, 16, 24, 32, 40 and 48. Nutrient adequacy and dietary diversity score (DDS) were calculated. Generalised estimating equations were used to assess the effects of total nutrient intakes, DDS, ONS compliance and sociodemographic factors on longitudinal growth. The percentages of children with adequate intake of energy, protein, Fe, Ca and some vitamins at each post-baseline visit were improved from baseline, reaching 100 % for most nutrients. DDS was also increased from baseline and reached significance from week 16 onwards (P < 0·01). Male children, total energy intake and parental employment status were associated with weight-for-height percentile gain (P < 0·05), whereas higher parental education level and ONS compliance were significantly associated with height-for-age percentile gain over time (P < 0·05). Long-term ONS intervention did not interfere with normal food intake and helped promote nutritional adequacy and growth of Filipino children.